Genome-wide interaction analysis reveals replicated epistatic effects on brain structure - Hibar, Derrek P. (Neurobiol Aging, 2014)
The discovery of several genes that affect risk for Alzheimer's disease ignited a worldwide search for Single Nucleotide Polymorphisms (SNPs), common genetic variants that affect the brain. Genome-wide search of all possible SNP-SNP interactions is challenging and rarely attempted, due to the complexity of conducting ∼10(11) pairwise statistical tests. However, recent advances in machine learning, e.g., iterative sure independence screening (SIS), make it possible to analyze datasets with vastly more predictors than observations. Using an implementation of the SIS algorithm (called EPISIS), we performed a genome-wide interaction analysis testing all possible SNP-SNP interactions affecting regional brain volumes measured on MRI and mapped using tensor-based morphometry. We identified a significant SNP-SNP interaction between rs1345203 and rs1213205 that explains 1.9% of the variance in temporal lobe volume. We mapped the whole-brain, voxelwise effects of the interaction in the ADNI dataset and separately in an independent replication dataset of healthy twins (QTIM). Each additional loading in the interaction effect was associated with ∼5% greater brain regional brain volume (a protective effect) in both ADNI and QTIM samples.